Functional bowel disorders with diarrhoea: Clinical guidelines of the United European Gastroenterology and European Society for Neurogastroenterology and Motility. Issue 6 (13th June 2022) - Savarino, Edoardo; Zingone, Fabiana; Barberio, Brigida; Marasco, Giovanni; Akyuz, Filiz; Akpinar, Hale; Barboi, Oana; Bodini, Giorgia; Bor, Serhat; Chiarioni, Giuseppe; Cristian, Gheorghe; Corsetti, Maura; et al.
Abstract: Irritable bowel syndrome with diarrhoea (IBS‐D) and functional diarrhoea (FDr) are the two major functional bowel disorders characterized by diarrhoea. In spite of their high prevalence, IBS‐D and FDr are associated with major uncertainties, especially regarding their optimal diagnostic work‐up and management. A Delphi consensus was performed with experts from 10 European countries who conducted a literature summary and voting process on 31 statements. Quality of evidence was evaluated using the grading of recommendations, assessment, development, and evaluation criteria. Consensus (defined as >80% agreement) was reached for all the statements. The panel agreed with the potential overlapping of IBS‐D and FDr. In terms of diagnosis, the consensus supports a symptom‐based approach also with the exclusion of alarm symptoms, recommending the evaluation of full blood count, C‐reactive protein, serology for coeliac disease, and faecal calprotectin, and consideration of diagnosing bile acid diarrhoea. Colonoscopy with random biopsies in both the right and left colon is recommended in patients older than 50 years and in presence of alarm features. Regarding treatment, a strong consensus was achieved for the use of a diet low fermentable oligo‐, di‐, monosaccharides and polyols, gut‐directed psychological therapies, rifaximin, loperamide, and eluxadoline. A weak or conditional recommendation was achieved for antispasmodics, probiotics, tryciclic antidepressants, bile acid sequestrants, 5‐hydroxytryptamine‐3 antagonists (i.e. alosetron, ondansetron, or ramosetron). A multinational group of European experts summarized the current state of consensus on the definition, diagnosis, and management of IBS‐D and FDr.